Templated synthesis of cubic crystalline single networks having large open-space lattices by polymer cubosomes - Yunju La (Nature Portfolio, 2018)
Cubic crystalline single networks of large open-space lattices are ubiquitous in nature. Here the authors show that the topology of the circumferential bilayer of polymer cubosomes differentiates between two non-intersecting pore networks embedded in the cubic mesophase by sealing one channel network at the interface.